GLOBAL SUPPLY CHAIN RISK IMPACT MEASUREMENT SYSTEM ON FINANCIAL PERFORMANCE - Riduan Siagian; Jumadiah Wardati; Nana Soraya (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This study aims to develop and test an impact measurement system that integrates global supply chain risks with a company's financial performance. Supply chain risk—originating from both internal and external factors—can cause operational disruptions such as process failures and shipping delays, increase operational costs, and disturb cash flows, thereby affecting financial performance indicators. Specifically, the research examines the effects of operational risk, financial risk, geopolitical risk, and environmental risk on financial performance measures including Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), Current Ratio (CR), and Debt to Equity Ratio (DER). The methodology applies a quantitative approach using Structural Equation Modeling (SEM) with AMOS, along with scenario analysis and what-if simulation to assess the impact of specific disruptions—for example, a 20% increase in logistics costs or critical shipment delays. The findings indicate that financial risk and operational risk are the dominant factors exerting significant negative effects on financial performance: financial risk notably reduces ROA and ROE, while operational risk affects NPM through increased costs and margin compression. Geopolitical and environmental risks, although showing more moderate effects, still influence overall operational stability and financial performance. The study provides managerial implications, including supplier diversification, implementation of Supply Chain Finance (SCF), adoption of real-time monitoring technologies (eg, IoT and predictive analytics), and formulation of contingency plans and risk-specific mitigation strategies.